2018
DOI: 10.1002/tafs.10021
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Interactions between Fishes in a Coastal Ecosystem in the Southern Gulf of St. Lawrence, Atlantic Canada

Abstract: Diet composition, diet similarity, and major predator–prey interactions between the 15 most abundant demersal and pelagic fishes (N = 12,163 stomachs) during the period 1999–2003 were described for Northumberland Strait, a semi‐enclosed, marine coastal ecosystem. Of the five pelagic species, Rainbow Smelt Osmerus mordax ate benthic prey (shrimps and polychaetes); Atlantic Herring Clupea harengus and American Shad Alosa sapidissima consumed small copepods and crab zoeae; and Atlantic Mackerel Scomber scombrus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 100 publications
(308 reference statements)
0
3
0
Order By: Relevance
“…In the reviewed studies, prey items were analyzed either individually or were aggregated into groups according to taxonomic status, functional characteristics, body size (e.g., Oakley et al, 2014), life history stage (e.g., Whitehouse et al, 2017), or association with different habitat types and depth (e.g., Giraldo et al, 2017). Similarly, the biological traits of the sampled predators, such as body or gape size, and ontogenetic shifts in feeding (e.g., Abdurahiman et al, 2010;French et al, 2013;Dunic and Baum, 2017;Hanson, 2018) were taken into account in some studies, to allow a more detailed assessment of the feeding habits of a species. The consideration of such biotic traits were sometimes also used to aggregate species into trophic guilds (non-taxonomic groups of species which exploit the same resources; Abdurahiman et al, 2010;Whitehouse et al, 2017;Hanson, 2018), estimate trophic spectra (e.g., Torruco et al, 2007), and calculate indices which were used as basic inputs in respective food web models (e.g., the consumption per biomass ratio; Ullah et al, 2018).…”
Section: Methodological Aspectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the reviewed studies, prey items were analyzed either individually or were aggregated into groups according to taxonomic status, functional characteristics, body size (e.g., Oakley et al, 2014), life history stage (e.g., Whitehouse et al, 2017), or association with different habitat types and depth (e.g., Giraldo et al, 2017). Similarly, the biological traits of the sampled predators, such as body or gape size, and ontogenetic shifts in feeding (e.g., Abdurahiman et al, 2010;French et al, 2013;Dunic and Baum, 2017;Hanson, 2018) were taken into account in some studies, to allow a more detailed assessment of the feeding habits of a species. The consideration of such biotic traits were sometimes also used to aggregate species into trophic guilds (non-taxonomic groups of species which exploit the same resources; Abdurahiman et al, 2010;Whitehouse et al, 2017;Hanson, 2018), estimate trophic spectra (e.g., Torruco et al, 2007), and calculate indices which were used as basic inputs in respective food web models (e.g., the consumption per biomass ratio; Ullah et al, 2018).…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…Similarly, the biological traits of the sampled predators, such as body or gape size, and ontogenetic shifts in feeding (e.g., Abdurahiman et al, 2010;French et al, 2013;Dunic and Baum, 2017;Hanson, 2018) were taken into account in some studies, to allow a more detailed assessment of the feeding habits of a species. The consideration of such biotic traits were sometimes also used to aggregate species into trophic guilds (non-taxonomic groups of species which exploit the same resources; Abdurahiman et al, 2010;Whitehouse et al, 2017;Hanson, 2018), estimate trophic spectra (e.g., Torruco et al, 2007), and calculate indices which were used as basic inputs in respective food web models (e.g., the consumption per biomass ratio; Ullah et al, 2018). Gut content analysis was also used to verify or complement dietary information obtained through other types of trophic level determination techniques, such as stable isotope or fatty acids analysis (e.g., Rodríguez-Graña et al, 2008;Paiva et al, 2013), to estimate bioaccumulation levels of heavy metals (e.g., McMeans et al, 2015), and to build up complex ecosystem-based models (e.g., Lassalle et al, 2011).…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…In contrast, copepods showed a notable reduction in δ 13 C values during the most recent period, with American sand lance, mainly a consumer of copepods (Staudinger et al., 2020 ), and capelin (Chamberland et al., 2022 ; Dalpadado & Mowbray, 2013 ) both echoing this trend. However, other secondary consumers (e.g., Arctic cod, Atlantic herring, and fin whales) known to feed to some extent on copepods and euphausiids but also on other species (Cabrol et al., 2021 ; Darbyson et al., 2003 ; Hanson, 2018 ; Nelson et al., 2020 ), varied in the direction of their isotopic shifts during the most recent period, challenging the possibility of a shift in the ecosystem baseline. A study tracking parallel changes in DIC and DIN concentrations and in isotopic signature of community constituents up to secondary consumers over time indicated that isotopic variations attenuate rapidly with trophic level (Gavrilchuk et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%